Histological changes in gills and liver of fishes in river Sutlej as an effect of Buddha Nullah pollution at Ludhiana. - Aditi Jaidka; Hundal SS (International Journal of Life Sciences, 2017)
Buddha nullah serves as a reservoir of industrial and sewage effluents of Ludhiana, Punjab containing high levels of toxic chemical discharged directly into river Sutlej. This leads to deterioration in the water quality and is a serious threat to fish fauna of the river. The study aims to investigate the level of changes in the histological architecture of gills and liver of fish from 3 sampling sites - 2km downstream in river Sutlej after the confluence with Buddha Nullah, 2 km upstream in river Sutlej after the confluence with Buddha Nullah and 5 km upstream in river Sutlej after the confluence with Buddha Nullah caused by Buddha Nullah pollution. Significantly higher histological abnormalities were observed in fish species collected from downstream area than upstream. Complete secondary lamellar fusion, breakage and degeneration of secondary epithelium, detachment of secondary epithelium, necrosis of lamellae, vasodilation of secondary lamellae, haemorrhage and vasodilation in primary lamellae were found in the gills of fish inhabiting polluted waters. In contrast, fish captured from 5 km upstream site (non polluted site) showed milder alterations limited to ruptured secondary epithelium only. Histology of liver showed vacuolization of hepatocytes, degenerative hepatocytes, necrosis and disruption of normal architecture in the fish from polluted sites whereas the sections of the tissues from fish collected from non polluted site of the river Sutlej exhibit a normal structure of hepatocytes with a rare occurance of mild necrosis The study clearly exhibits the deleterious effect fish vital organs even after a small extent of exposure to contaminated natural waters.